2019
DOI: 10.1007/s00415-019-09561-0
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and gustatory functioning and food preferences of patients with Alzheimer’s disease and mild cognitive impairment compared to controls: the NUDAD project

Abstract: Our aim is to compare olfactory and gustatory function and food preferences of patients with Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) with controls. We included 22 patients with MCI, 30 patients with AD and 40 controls and assessed olfactory threshold, odor discrimination and odor identification (Sniffin' Sticks), gustatory functioning (Taste Strips), and food preferences (Macronutrient and Taste Preference Ranking Task). Linear regression analyses were used to study associations of five co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 46 publications
(43 reference statements)
3
22
0
Order By: Relevance
“…[ 72 ]). Similar results were also obtained by other groups [ 44 , 68 , 91 ], reporting significantly lower odor identification ability of 60–75-year-old AD patients compared to age-matched controls.…”
Section: Early Olfactory Impairment In Patients With Alzheimer’s Disesupporting
confidence: 90%
See 3 more Smart Citations
“…[ 72 ]). Similar results were also obtained by other groups [ 44 , 68 , 91 ], reporting significantly lower odor identification ability of 60–75-year-old AD patients compared to age-matched controls.…”
Section: Early Olfactory Impairment In Patients With Alzheimer’s Disesupporting
confidence: 90%
“…This difference, however, did not reach the level of statistical significance. A recent study on somewhat younger AD patients (69.5 ± 9.4 years old) also failed to find any difference in the odor threshold sensitivity between AD patients and the age-matched (62.5 ± 6.8 years old) control group [ 44 ].…”
Section: Early Olfactory Impairment In Patients With Alzheimer’s Disementioning
confidence: 99%
See 2 more Smart Citations
“…Concerning other olfactory functions, a recently published study (Lian et al, 2019) investigated the relationship between the threshold discrimination identification score and CSF Aβ and tau levels in AD patients with or without olfactory dysfunction (OD), finding that only t-tau levels were significantly lower in the AD-OD group, but the significant correlation disappeared after adjusting for age, sex, education, and disease duration. The same was true for the study by Doorduijn et al (2020), which found no associations between AD biomarker levels and threshold discrimination identification. Another excluded study using odor percept identification performance with a homemade test to correlate with Aβ PET data also yielded a negative result (Dhilla Albers et al, 2016).…”
Section: Discussionsupporting
confidence: 57%